A NARRATIVE REVIEW OF ZINGIBERACEAE FAMILY AS ANTIBACTERIAL AGENT FOR TRADITIONAL MEDICATION BASED ON BALINESE LOCAL WISDOM - Irayanti, Ayu; Yadnya Putra, A.A Gede Rai (Journal Pharmaceutical Science and Application; Vol 2 No 2 (2020): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2020.v02.i02.p04, 2020)
Background: One of the native plants from Indonesia that have been widely used for traditional medication as an antibacterial comes from the Zingiberaceae family. Based on Usada Bali, the Zingiberaceae family used to treat digestive, respiratory, and skin diseases. Objective: This literature review aimed to discuss antibacterial activity from the Zingiberaceae family and see its validity as a traditional use as antibacterial based on Balinese local wisdom medication method (Usada) with its scientific evidence. Methods: The method of this literature review is the study of literature from several scientific publications in national and international journals about the antibacterial activity of the Zingiberaceae family. Results: Several studies showed that the Zingiberaceae family has an antibacterial activity with various inhibitions depended on the type of bacteria. Conclusion: The Zingiberaceae family mentioned in Usada Bali has been scientifically proved to have antibacterial activity, so it shows the validity as a traditional use as antibacterial based on Usada with its scientific evidence. Keywords: Zingiberaceae, antibacterial, Usada